Democratização social e pluralidade de sujeitos políticos: uma leitura a partir da teoria democrática radical e plural - Frederico Alves Costa (2010)
With the emergence of a plurality of political subjects since the 1960s, along with the various theories, critics and critiques that have followed, a tension has arisen in the dialogue about the multiple identities held by political subjects. The debate asks the question of how strategies among different political subjects can be constructed in such a way that thesesubjects do not dissipate themselves in the experience of identities, neither segregating themselves due to their particularities nor losing their autonomy through the affirmation of a universality that denies liberty for the sake of equality. Having this tension as a starting point, the objective of this dissertation is to discuss possible strategies to confront the set of hegemonic logics leading to those conditions of inequality andexclusion that continually reproduce sub-citizenship in its many forms. With this in mind, we have the following research problems to explore: what possibilities of social democratization have been built as a result of the de-centralization of the political space and the plurality ofpolitical subjects? How does the Left view its own political unity in this new political landscape? What strategies have been developed in order to fight the different forms of inequalities and politicized exclusions as means of oppression in the present time, so as to build a counter-hegemonic struggle? These research problems have been analyzed within the theoretical framework of the Radical and Plural Democratic Theory developed by Chantal Mouffe and Ernesto Laclau; as well as through empirical data collected from group representatives of different social movements, including both semi-structured interviews and related documentation. Using the key concepts of the Radical and Plural Democratic Theory such as articulation, equivalence logic, difference logic, and displacement we discuss two possible strategies for social movements to face the hegemonic logics leading to conditions of sub-citizenship: articulation strategy and alliance strategy. We also analyze two ways through which the dominant hegemony weakens political struggles aimed at building antagonistic alternativesfor society, referred to as expansion of the hegemony and exclusion by difference. Furthermore, we discuss the conceptual development of History and historical subject within the process of social democratization in Brazilian society, as well as the forms ofaction that are considered fundamental in order to achieve a more pluralistic and democratic society.